2005
DOI: 10.1177/0269881105051529
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of clonidine and temazepam on attention and memory

Abstract: The present study compared the effects of clonidine and temazepam on performance on a range of tasks aiming to assess the role of central noradrenergic mechanisms in cognitive function. Fifteen healthy volunteers (seven male, eight female), aged 18-25 years, took part in a five-period crossover study in which they received placebo, temazepam (15 and 30 mg) and clonidine (150 and 300 microg) by mouth in counterbalanced order in sessions at least 4 days apart. A test battery was administered before treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
(40 reference statements)
1
20
0
Order By: Relevance
“…In one study, lower and higher doses of clonidine (0.04 and 0.4 mg) impaired working memory but an intermediate dose (0.16 mg) had no effect (Jakala et al 1999a). In another, the deleterious effects of clonidine were more marked at a higher compared to a lower dose (0.30 vs 0.15 mg) (Tiplady et al 2005). In another investigation, Coull et al (1995b) found that 0.12 mg clonidine had no effect on spatial working memory but impaired visual working memory, whereas 0.20 mg improved spatial working memory with no effect on visual working memory.…”
Section: Effects Of Na Manipulations On Working Memorymentioning
confidence: 94%
“…In one study, lower and higher doses of clonidine (0.04 and 0.4 mg) impaired working memory but an intermediate dose (0.16 mg) had no effect (Jakala et al 1999a). In another, the deleterious effects of clonidine were more marked at a higher compared to a lower dose (0.30 vs 0.15 mg) (Tiplady et al 2005). In another investigation, Coull et al (1995b) found that 0.12 mg clonidine had no effect on spatial working memory but impaired visual working memory, whereas 0.20 mg improved spatial working memory with no effect on visual working memory.…”
Section: Effects Of Na Manipulations On Working Memorymentioning
confidence: 94%
“…This may be why, for example, in a study that used task comparison to determine which processes are affected by clonidine versus temazepam (known to have different pharmacological mechanisms) in which 11 tasks were used, each drug produced statistically significant effects on all except one of the tasks (Tiplady, Bowness, Stien, & Drummond, 2005). The processdecomposition approach might be more helpful.…”
Section: Donders' Subtraction Method: Task Comparison With a Compositmentioning
confidence: 99%
“…The Arrow Flankers task 33 consisted of five stimuli presented in a row in the center of the screen and lasted 3 minutes. Participants were instructed to press left [4] or right [6] keys on the keypad corresponding to the direction of the central arrow as quickly as possible while ignoring the flankers, unless the flankers were crosses in which case participants were instructed not to respond.…”
Section: Neurobehavioral Performancementioning
confidence: 99%